Budaya Organisasi pada Dinas Pendidikan dan Kebudayaan Kabupaten Padang Pariaman - Karnila; Ermita, Ermita; Tia Ayu Ningrum; Enceria Damanik (CV. ITTC INDONESIA, 2026)
This research is motivated by the results of the researcher's observations that the Organizational Culture in the Department of Education and Culture of Padang Pariaman Regency is still not good. This study aims to find out and obtain information about (1) Values ​​that apply within the organization, (2) Employee trust/belief in the organization, (3) Employee self-awareness in working, (4) Employee behavior in working in the Department of Education and Culture of Padang Pariaman Regency. The type of research used is descriptive quantitative with a population of 115 people. Sampling in this study is Probability sampling or simple random sampling, taking sample members from the population is done randomly without paying attention to the strata in the population. The research instrument used is a questionnaire with a Likert scale model with five alternative answers: always (SL), often (SR), sometimes (KD), rarely (JR), never (TP). Before the questionnaire was used, it was first tested to determine its validity and reliability. The results of the validity test showed two invalid statements, but this study remains reliable. The data analysis technique uses the Mean formula (average score). The results of the study show that the organizational culture at the Padang Pariaman Regency Education and Culture Office is seen from the following indicators: (1) The values ​​that apply within the organization are good and the average score is (3.68), (2) Employee trust/belief in the organization is good and the average score is (3.63), (3) Employee self-awareness in working is good and the average score is (3.73), (4) Employee behavior in working is good and the average score is (3.70). (5) Organizational Culture at the Padang Pariaman Regency Education and Culture Office has been implemented well.